Strategic Partnership Between The Police and Society in Realizing Indonesia Gold: Challenges and Opportunities - Rudy Cahya Kurniawan (Jurnal Penelitian Pendidikan, 2024)
Indonesia is in the midst of a journey towards the grand vision of Indonesia Emas 2045, one of the main pillars of which is the stability of security and public order. The purpose of writing this scientific paper is to evaluate the role and challenges in the strategic partnership between the National Police and the community in supporting the vision of Indonesia Emas, as well as to formulate strategies to strengthen the partnership and overcome existing obstacles. The conclusion of this paper is that the role of the National Police in building strategic partnerships with the community is very important to support the vision of Indonesia Emas, but challenges such as lack of trust and ineffective communication need to be overcome. Strengthening partnerships can be done by utilizing opportunities and implementing strategies based on transparency, accountability, and effective communication. The suggestions in this paper are for the National Police to strengthen community-based partnership programs, develop education and training programs, increase collaboration with civil society organizations, implement fair conflict resolution mechanisms, and conduct periodic evaluations and adjustments to strategies to increase the effectiveness of partnerships with the community.